Cost Impact Model of a Novel Multi-mRNA Host Response Assay for Diagnosis and Risk Assessment of Acute Respiratory Tract Infections and Sepsis in the Emergency Department - John E. Schneider; Jonathan Romanowsky; Philipp Schuetz; Ivana Stojanovic; Henry K. Cheng; Oliver Liesenfeld; Ljubomir Buturovic; Timothy E. Sweeney (Journal of Health Economics and Outcomes Research)
**Background:** Early identification of acute infections and sepsis remains an unmet medical need. While early detection and initiation of treatment reduces mortality, inappropriate treatment leads to adverse events and the development of antimicrobial resistance. Current diagnostic and prognostic solutions, including procalcitonin, lack required accuracy. A novel blood-based host response test, HostDx™ Sepsis by Inflammatix, Inc., assesses the likelihood of a bacterial infection, the likelihood of a viral infection, and the severity of the condition.